Cachez ce care que je ne saurais voir. Les ajustements méthodologiques d’une étude féministe du travail du care dans le logement collectif - Benjamin Leclercq; Audrey Courbebaisse; Ansao Totolehibe; Chloé Salembier (GéoProximitéS)
Making domestic and care work visible, quantifying and qualifying in order to recognize, distribute, share, value or outsource it among the society has been one of the major challenges of the feminist project for decades. This article discusses the methodological implications of objectifying and spatialising domestic and care work in residential environment. To date, most care work’s studies have neglected its spatial dimension, or have focused on scales that are too broad to highlight the links between relational work and work on space. As part of a research project carried out in the Brussels-Capital Region on seven private or public housing estates, a twofold proposal is put forward and its obstacles and difficulties tested: the “inhabited survey” as a methodology for collecting spatialised data on care, and the visualisation diagram as a means of representing inhabitant practices linked to care. Showing care implies, on the one hand, shaking up our methods of data collection and visualisation and, on the other hand, spatialising it so that it can be better considered in housing and urban policies.